A Ruthenium(II) Polypyridyl Complex Disrupts Actin Cytoskeleton Assembly and Blocks Cytokinesis. Issue 27 (3rd May 2022) - Gill, Martin R.; Jarman, Paul J.; Hearnden, Vanessa; Fairbanks, Simon D; Bassetto, Marcella; Maib, Hannes; Palmer, John; Ayscough, Kathryn R.; Thomas, Jim A.; Smythe, Carl
Abstract: The dinuclear Ru II complex [(Ru(phen)2 )2 (tpphz)] 4+ (phen=1, 10‐phenanthroline, tpphz=tetrapyridophenazine) "RuRuPhen" blocks the transformation of G‐actin monomers to F‐actin filaments with no disassembly of pre‐formed F‐actin. Molecular docking studies indicate multiple RuRuPhen molecules bind to the surface of G‐actin but not the binding pockets of established actin polymerisation inhibitors. In cells, addition of RuRuPhen causes rapid disruption to actin stress fibre organisation, compromising actomyosin contractility and cell motility; due to this effect RuRuPhen interferes with late‐stage cytokinesis. Immunofluorescent microscopy reveals that RuRuPhen causes cytokinetic abscission failure by interfering with endosomal sorting complexes required for transport (ESCRT) complex recruitment. Abstract : The dinuclear Ru II complex [(Ru(phen)2 )2 (tpphz)] 4+ binds to G‐actin monomers, preventing assembly into F‐actin. This inhibits actin fibre assemblies within live cells and causes disruption to late cytokinesis by interfering with the function of endosomal sorting complexes required for transport (ESCRT) during abscission. These results reveal new possibilities for metal complexes as biomedical tools and novel therapeutic leads.